IMPLEMENTASI DIMENSI KUALITAS DAN DAMPAKNYA TERHADAP KINERJA ORGANISASI (Studi Pada Perusahaan-perusahaan Besar dan Sedang di Malang Jawa Timur) - Syaiful Arifin; Tri Wahyuni (University of Merdeka Malang, 2016)
This researchanalyzes theinfluence of thevariousdimensions ofqualityon the company performance.The source of data research are 75 companies composed of 46 major companies and 29 medium companies.The datacollected through middlemanagers and top managers of major and medium companiesin Malang, East Java.The results showed thatthe dimension ofquality (customer satisfaction,employee satisfactionandemployeeservicequality)effectsignificantly toorganizational performanceat both themajor companiesand medium companies .The service quality of employee has a dominant effect to the performance ofthe company.